1974
DOI: 10.1002/lary.5540841119
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic complications of facial fractures

Abstract: Two hundred ninety‐six facial fracture patients, exclusive of nasal fracture patients treated on an out‐patient basis, came to the Medical College of Virginia Hospitals between January 1, 1970, and December 31, 1972. The various managing services, age and sex of the patients, and the months of occurrences were tabulated. Of interest were six patients who had a hemorrhagic complication after adequate surgical reduction — about a 2 percent incidence. All six patients sustained fractures of the fronto‐naso‐ethmoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…3,4 According to the literature, the incidence of mas- sive bleeding in maxillofacial trauma tends to increase in complex fractures associated with midface fractures. [5][6][7][8][9][10][11] The present study also found a significant correlation between Le Fort fractures and massive bleeding in the maxillofacial region (9.61%). Furthermore, we found that the most frequent source of massive bleeding in midfacial fractures was the nose, which bled through the oral cavity.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…3,4 According to the literature, the incidence of mas- sive bleeding in maxillofacial trauma tends to increase in complex fractures associated with midface fractures. [5][6][7][8][9][10][11] The present study also found a significant correlation between Le Fort fractures and massive bleeding in the maxillofacial region (9.61%). Furthermore, we found that the most frequent source of massive bleeding in midfacial fractures was the nose, which bled through the oral cavity.…”
Section: Discussionsupporting
confidence: 48%
“…In fact, death from such injuries has been reported. 5,6 Frable et al 7 found that among 296 patients with midfacial fractures, 9.4% developed severe bleeding. Among 312 facial fractures reviewed by Buchanan and Holtmann, 8 12 (11%) of 108 had midfacial fractures.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is a rare complication of midfacial fractures with a reported incidence of 9.4% (2). It can cause life-threatening blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In patients with massive bleeding refractory to conventional therapy, such as manual pressure and nasal packing, the compromised airway and profound shock status often are the major cause of mortality. Percutaneous endovascular treatments, such as transarterial embolization (TAE), have emerged as the rescue choice for intractable nasal bleeding since their successful introduction to intractable epistaxis in emergency or elective cases.…”
mentioning
confidence: 99%